1999
DOI: 10.1074/jbc.274.25.18113
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects on Secretion in Chromaffin and PC12 Cells of Rab3 Family Members and Mutants

Abstract: The Rab class of low molecular weight GTPases has been implicated in the regulation of vesicular trafficking between membrane compartments in eukaryotic cells. The Rab3 family consisting of four highly homologous isoforms is associated with secretory granules and synaptic vesicles. Many different types of experiments indicate that Rab3a is a negative regulator of exocytosis and that its GTP-bound form interacts with Rabphilin3, a possible effector. Overexpression of Rabphilin3 in chromaffin cells enhances secr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
35
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(44 citation statements)
references
References 58 publications
8
35
1
Order By: Relevance
“…Noc2 binding was specific for Rab3A, as the endosome-specific Rab5B failed to associate in the presence of GTP␥S. The affinity of the interaction (ϳ500 nm) was lower than that reported for Rabphilin binding to Rab3A of 150 nM (43) or 20 nM (33). This may explain the low efficiency of binding in the in vitro assay that we observed.…”
Section: Figcontrasting
confidence: 53%
See 2 more Smart Citations
“…Noc2 binding was specific for Rab3A, as the endosome-specific Rab5B failed to associate in the presence of GTP␥S. The affinity of the interaction (ϳ500 nm) was lower than that reported for Rabphilin binding to Rab3A of 150 nM (43) or 20 nM (33). This may explain the low efficiency of binding in the in vitro assay that we observed.…”
Section: Figcontrasting
confidence: 53%
“…This effect is not directly mediated by the interaction with Rab3A, as point mutants in Rabphilin3A having defective Rab3A binding still enhance secretion from an endocrine cell line (31). In a reciprocal study (33), Rab3A mutants defective in Rabphilin3A binding retained the wild type ability to inhibit secretion. Further evidence for a Rab3A-independent effect of Rabphilin 3A comes from studies using Rabphilin 3A knockout mice (34).…”
Section: Figmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that Rab8a is not involved in the regulated secretory pathway that involves the apical or axonal surfaces. Furthermore, studies have demonstrated that overexpression of Rab8a has no effect on the regulated secretion of human growth hormone (37). In contrast, the overexpression of Rab8b had a significant stimulatory effect on the regulated secretion of ACTH that occurs at the tips of the cell processes (13,38).…”
Section: Rab8b and Trip8b Stimulate Acth Releasementioning
confidence: 99%
“…The Rab3 family consists of four highly homologous isoforms associated with secretory granules and synaptic vesicles. Overexpression of each of the four members of the Rab3 family inhibited secretion (37). Moreover, knockout of Rab3A increased the quantal release of synaptic vesicles (39).…”
Section: Rab8b and Trip8b Stimulate Acth Releasementioning
confidence: 99%